Translation Skills In French-Uzbek Literature Relations (on the Example of The Uzbek Translation of Albert Camus's "Plague") - Sayfulloev Bakhshillo Nematulloevich (Indonesian Journal of Innovation Studies, 2022)
This article deals with the French-Uzbek literary relations of the independence period. Unda A. The Uzbek translation of Camus's novel Plague will be analyzed, with special emphasis on translation skills.